2022
DOI: 10.3389/fphar.2022.953845
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in circulating PCSK9 and its clinical implications

Abstract: Proprotein convertase subtilisin kexin type 9 (PCSK9) is a proprotein convertase that increases plasma low-density lipoprotein cholesterol (LDL-C) levels by triggering the degradation of LDL receptors (LDLRs). Beyond the regulation of circulating LDL-C, PCSK9 also has direct atherosclerotic effects on the vascular wall and is associated with coronary plaque inflammation. Interestingly, emerging data show that women have higher circulating PCSK9 concentrations than men, suggesting that the potential roles of PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Regarding LDL-C levels, the SNP is sex-biased as we described it for PCSK9, with stronger effects in men (p IA = 5.38 × 10 –5 using the GLGC data [ 8 ]). In summary, this suggests sex-regulated transcription and translation of PCSK9, which could contribute to the observed sexual dimorphism of PCSK9 levels with higher levels observed in women [ 6 ]. The third independent signal, rs11583680, displayed a significant 2-way statin-interaction with the strongest effect in statin-treated men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding LDL-C levels, the SNP is sex-biased as we described it for PCSK9, with stronger effects in men (p IA = 5.38 × 10 –5 using the GLGC data [ 8 ]). In summary, this suggests sex-regulated transcription and translation of PCSK9, which could contribute to the observed sexual dimorphism of PCSK9 levels with higher levels observed in women [ 6 ]. The third independent signal, rs11583680, displayed a significant 2-way statin-interaction with the strongest effect in statin-treated men.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphisms are common in lipid metabolism, and PCSK9 also exhibits sex-differential behavior with women having higher circulating PCSK9 concentrations than men [ 6 , 7 ]. While large-scale sex-stratified genome-wide association meta-analyses (GWAMA) were already performed for the common lipid traits such as: total cholesterol (TC), LDL-C, high-density lipoprotein cholesterol (HDL-C), triglycerides, and non-HDL-C [ 8 ], so far there was no GWAS on stratified PCSK9 levels to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, emerging data show that women have higher circulating PCSK9 concentrations than men, suggesting that the potential roles of PCSK9 may have different impacts according to sex. 230 In a large European cohort of individuals ( n = 3673, aged 54–79 years) free of cardiovascular diseases enrolled in seven centres of five European countries: Finland, France, Italy, the Netherlands, and Sweden, PCSK9 plasma level was higher in women than in men. 231 Another study among Thai subjects confirmed that PCSK9 concentrations were significantly higher in women than in men ( P = 0.002).…”
Section: Proprotein Convertase Subtilisin Kexin Typementioning
confidence: 99%
“…Even when women with FH are prescribed PCSK9 inhibitors, women compared to men show less LDL-C reduction of PCSK9 inhibitors [ 34 , 35 ]. A reason for this sex difference may be related to the influence of estrogens on PCSK9 levels through G-protein coupled estrogen receptors on the hepatocytes, and this should be further investigated [ 36 , 37 ].…”
Section: Treatmentmentioning
confidence: 99%